A THEORETICAL STUDY OF THE ROLE OF INTERNAL AUDIT IN FRAUD PREVENTION IN THE DIGITAL AGE - Silfanawati A. Dumo; Fitriana S. Salmin; Zein Luadu; Habiba Habiba; Sahmin Noholo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Advances in digital technology have brought significant changes to organizational activities; however, they have also increased the risk of technology-based fraud, such as cyber fraud, data manipulation, phishing, and misuse of information systems. These conditions require organizations to strengthen the internal audit function as a critical component of internal controls and fraud prevention. This study aims to theoretically examine the role of internal audit in preventing fraud in the digital era. The research method used is a systematic literature review (SLR) by collecting and analyzing various relevant national and international journals from 2020 to 2026. The analysis process was conducted using qualitative descriptive methods through the identification, selection, and grouping of research findings based on discussion themes. The research findings indicate that internal audit plays a strategic role in identifying risks, conducting oversight, evaluating the effectiveness of internal controls, and supporting the implementation of good corporate governance. The utilization of audit technologies, such as data analytics, continuous auditing, and digital-based monitoring systems, has proven capable of enhancing the effectiveness of fraud detection and prevention more quickly and accurately. This study also found that the digital competencies of internal auditors and the company’s readiness to strengthen its internal control systems are key factors in supporting the effectiveness of internal audits in the digital age. The implications of this study suggest that organizations need to enhance the competencies of internal auditors and strengthen technology-based internal controls to address increasingly complex digital fraud risks.